ANALISIS METABOLIT SEKUNDER DAN KANDUNGAN NUTRISI DARI MAKROALGA HIJAU (Chlorophyceae) DI PERAIRAN TELUK KUPANG - Winda Nome; Yuliana Salosso; Cresca Benmar Eoh (Jurnal Akuatik, 2019)
This study aims to determine the types of green macroalgae were found in waters Kupang Bay and content of secondary metabolites and nutritional composition. The method used in this research that green macroalgae species that serve as the research object, then perform analysis of the nutrient content and the amount of secondary metabolites found in the types of green macroalgae conducted at the Laboratory. The results of the research that has been done show that for every type of macroalgae green (Ulva sp, Entermorpha sp, Chaulerpha sp, Codium sp, Halimeda sp 2, Halimeda sp 3, Halimeda sp 1 and Halimeda sp 6) were found in the waters of the Gulf of Kupang everything there content of secondary metabolites such as alkaloids, saponins, flavonoids, tannins, Terpenoids and Steroids. But saponins are not on some kind of green macroalgae is Halimeda sp 1, Halimeda sp 3, sp Entermorpha, Ulva sp and sp Chaulerpha. Also Terpenoid content not found in macroalgae Chaulerpha sp. In addition to any kind of green macroalgae such tests have been conducted in which the nutritional content in the form of water content in the range of (5.78% to 43.27%), ash content (7.89% to 51.37%), protein content (6.55% -16.75%), levels of fat (1.41% to 2.92%), and levels of carbohydrates (18.12% to 55.88%). Keywords: Green macroalgae (Chlorophyceae), the secondary metabolites and nutrient content.